Anomalous couplings of the third generation in rare B decays - Burdman, Gustavo; Gonzalez-Garcia, M. C. [UNESP]; Novaes, Sérgio Ferraz [UNESP] (American Physical Soc, 2000)
We study the potential effects of anomalous couplings of the third generation quarks to gauge bosons in rare B decays. We focus on the constraints from flavor changing neutral current processes such as b→sγ and b →sl+l-. We consider both dimension-four and dimension-five operators and show that the latter can give large deviations from the standard model in the still unobserved dilepton modes, even after the bounds from b→sγ and precision electroweak observables are taken into account. ©2000 The American Physical Society.